Integrating frailty interventions into existing care models: a comprehensive approach to enhancing patient outcomes in chronic disease management - Uchmanowicz, Izabella; Faulkner, Kenneth M.; Iovino, Paolo; Kwaśny, Adrian; Surma, Stanisław; Magi, Camilla Elena; Jakubiak, Grzegorz K.; Longobucco, Yari; Janczak, Dawid; Rak-Pasikowska, Alina; Czapla, Michał; Uchmanowicz, Bartosz (Frontiers in Public Health, 2025)
Frailty syndrome (FS) is a complex and multifaceted condition commonly observed in old adults patients with chronic diseases, often accompanied by cognitive impairments. This review explores the integration of frailty interventions into existing care models to improve patient outcomes, focusing on four key areas. First, it emphasizes the importance of comprehensive assessment tools to identify frailty and cognitive impairments early, facilitating targeted care planning. Second, it highlights the value of personalized interventions, such as dietary modifications, exercise programs, and cognitive training, tailored to individual patient needs and preferences. Third, the review underscores the critical role of multidisciplinary care teams in providing holistic and coordinated care, leveraging the expertise of diverse healthcare professionals. Finally, it examines the potential of technological innovations and caregiver support systems in enhancing frailty management and addressing the challenges posed by cognitive impairments. By integrating these approaches, this review presents a patient-centered framework aimed at mitigating the impact of frailty and improving long-term outcomes. The findings emphasize the need for a unified strategy that combines personalized care, interdisciplinary collaboration, and technological advancements to address the multifaceted challenges of frailty in chronic disease management.